Development of a Shared UX Vision Based on UX Factors Ascertained Through Attribution. - Winter, Dominique; Hausmann, Carolin; Hinderks, Andreas; Thomaschewski, Jörg (International Journal of Interactive Multimedia and Artificial Intelligence, 2023)
User experience (UX) is an important quality in differentiating products. For a product team, it is a challenge to develop a good positive user experience. A common UX vision for the product team supports the team in making goal-oriented decisions regarding the user experience. This paper presents an approach to developing a shared UX vision. This UX vision is developed by the product team while a collaborative session. To validate our approach, we conducted a first validation study. In this study, we conducted a collaborative session with two groups and a total of 37 participants. The group of participants comprised product managers, UX designers and comparable professional profiles. At the end of the collaborative session, participants had to fill out a questionnaire. Through questions and observations, we identified ten good practices and four bad practices in the application of our approach to developing a UX vision. The top 3 good practices mentioned by the participants include the definition of decision-making procedures (G1), determining the UX vision with the team (G2), and using general factors of the UX as a basis (G3). The top 3 bad practices are: providing too little time for the development of the UX vision (B1), not providing clear cluster designations (B2) and working without user data (B3). The results show that the present approach for developing a UX vision helps to promote a shared understanding of the intended UX in a quickly and simply way.